ENGINEERING CHARACTERISTICS OF CORRUPTION IN THE ECONOMIC AND FINANCIAL FIELD, AND EFFECTIVENESS OF THE SHARES OF CONTROL IN GOVERNMENT INSTITUTIONS IN PERU - Gomero Gonzales, Nicko Alberto (2012)
Corruption has been responsible for apply a negative lobbying against economic growth; these illegal acts compromise the budgets and governments, and its effects could them dip out in continuous social and economic imbalances. Corruption is not a local phenomenon, but over the time has been perfected for its globalization and in this process has been present the technology; reflected in computer media that facilitated the actions of those who are not interested in the public good, only in his personal interest. Corruption has been responsible for generating of lost for Peruvian government in an average of 14 billion dollars, almost 50% of exports, this figure is the best sign that corrupt acts are still present in society and are continuing to exploit weaknesses that present legal meshes for its penalization. In this context, the aim of this article is to explain the economic and social effects of corruption, and the means of precision that used to avoid all kinds of administrative and criminal responsibilities.